Prevalence of antimicrobial resistance in urine, blood, and wound pathogens among rural patients in Karnataka, India - Markos Mardourian; Hannah Lyons; Jackson Rhodes Brunner; Matthew K. Edwards; Archibald Lennox; Sumana Mahadevaiah; Sunitha Chandrashekhar; Suvvada Prudhvi Raj; Anjali Pradhan; Gautam Kalyatanda (Cambridge University Press, 2023)
Abstract Background and objective: Antimicrobial resistance (AMR) is increasing in tertiary-care hospitals across India, which consumes more antibiotics than any other country. Microorganisms with novel resistance mechanisms, initially isolated in India, are now recognized worldwide. Until now, most efforts to stem AMR in India have focused on the inpatient setting. Ministry of Health data now suggest that rural areas are playing a more significant role in the pathogenesis of AMR than was previously appreciated. Thus, we conducted this pilot study to ascertain whether AMR is common in pathogens causing infections acquired in the wider rural community. Methods: We performed a retrospective prevalence survey of 100 urine, 102 wound, and 102 blood cultures obtained from patients who were admitted to a tertiary-care facility in Karnataka, India, with infections acquired in the community. The study population included patients >18 years of age who (1) were referred to the hospital by primary care doctors, (2) had a positive blood, urine, or wound culture, and (3) were not previously hospitalized. Bacterial identification and antimicrobial susceptibility testing (AST) were carried out on all isolates. Results: Enterobacteriaceae were the most common pathogens isolated from urine and blood cultures. Significant resistance to quinolones, aminoglycosides, carbapenems, and cephalosporins was noted among pathogens isolated from all cultures. Specifically, high resistance rates (>45%) to quinolones, penicillin, and cephalosporins were evident among all 3 types of culture. Among blood and urinary pathogens, there were high resistance rates (>25%) to both aminoglycosides and carbapenems. Conclusion: Efforts to stem AMR rates in India need to focus on rural populations. Such efforts will need to characterize antimicrobial overprescribing practices, healthcare-seeking behaviors, and antimicrobial use in agriculture in rural settings.